Evaluation of divinylsulfone activated agarose to immobilize lipases and to tune their catalytic properties. Issue 6 (June 2015) - dos Santos, Jose C.S.; Rueda, Nazzoly; Torres, Rodrigo; Barbosa, Oveimar; Gonçalves, Luciana R.B.; Fernandez-Lafuente, Roberto
Graphical abstract: Highlights: DVS agarose bead is a very suitable support to immobilize TLL. The immobilization protocol is critical to have good enzyme properties. The enzyme may be immobilized at different pH values. Further incubation at pH 10 improves stability. The pH of the first immobilization determines the final biocatalyst properties. Abstract: Divinylsulfone (DVS) activated agarose beads have been used to immobilize several lipases, those from Pseudomonas flourescens, Rhizomucor miehei, and Thermomyces lanuginosus (TLL), as well as the artificial chimeric phospholipase Lecitase Ultra. The best results in terms of activity recovery and immobilization yield were achieved using TLL. This enzyme could be immobilized at pH from 5 (with poor yield) to pH 10 (with 100% yield). The incubation of the immobilized enzymes for 72 h at pH 10 before the blocking step (using ethylenediamine) improved the enzyme stability whatever the immobilization pH value, but the stabilization achieved in each case depended on the immobilization pH value, and also on the inactivation conditions. The enzyme activities versus different substrates were very dependent on the immobilization protocol and the conditions of activity determination. That way, TLL immobilized at pH 5 on DVS activated support was the most active versus methyl mandelate, even more active than TLL immobilized on octyl-agarose (between 3 and 7 fold factors depending on the pH of measure). Using ethyl hexanoate the most active preparation was the octyl-TLL preparation. The most active among the enzymes immobilized in DVS-activated supports was that just immobilized at pH 5 if the activity was determined at pH 7 or 8.5, while at pH 5 the most active was that enzyme but after incubation at pH 10. The results show that this support may be very useful for tuning lipase properties just by altering the first immobilization pH value, and that the further incubation at pH 10 improved enzyme stability, and in some cases, even increased activity.